Knowledge of the Poznan region citizens about speech therapy profession - TRĘBACZ, AGATA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Agata Trębacz, Knowledge of the Poznan region citizens about speech therapy profession. Interdisciplinary Contexts of Special Pedagogy, no. 27, Poznań 2019. Pp. 197–221. Adam Mickiewicz University Press. ISSN 2300-391X. e-ISSN 2658-283X. DOI: https://doi.org/10.14746/ikps.2019.27.10 In recent years, the speech-language pathology has developed dynamically. It plays a growing role not only in the area of education but also in the field of medicine. Teaching correct articulation is just one of possible challenges faced by speechlanguage pathologists. The multidisciplinary context of that field of knowledge can be seen in various subfields of speech-language pathology which have evolved over time. Therefore, the primary objective of the conducted research was to assess the awareness of the importance of speech-language pathologists in everyday life of children and adults. The research was carried out among 50 respondents in the city of Poznań and provided the ground for discussion on the subject being the core issue of the presented paper.